Peptidoglycan Recognition Protein 2 Regulates Neutrophil Recruitment Into the Lungs After Streptococcus pneumoniae Infection - Dabrowski, Alexander N.; Conrad, Claudia; Behrendt, Ulrike; Shrivastav, Anshu; Baal, Nelli; Wienhold, Sandra M.; Hackstein, Holger; N’Guessan, Philippe D.; Aly, Sahar; Reppe, Katrin; Suttorp, Norbert; Zahlten, Janine (Frontiers in Microbiology, 2019)
Peptidoglycan (PGN) recognition proteins (PGLYRPs) are a highly conserved group of host defense proteins in insects and mammals that sense bacterial cell wall PGN and act bactericidally or cleave PGN by amidase function. Streptococcus (S.) pneumoniae is one of the top five killers worldwide and causes, e.g., pneumonia, endocarditis, meningitis and sepsis. S. pneumoniae accounts for approximately 1.5 to 2 million deaths every year. The risk of antibiotic resistance and a general poor prognosis in young children and elderly people have led to the need for new treatment approaches. To the best of our knowledge, there is no report on the relevance of PGLYRP2 in lung infections. Therefore, we infected mice deficient for PGLYRP2 transnasally with S. pneumoniae and examined the innate immune response in comparison to WT animals. As expected, PGLYRP2 KO animals had to be sacrificed earlier than their WT counterparts, and this was due to higher bacteremia. The higher bacterial load in the PGLYRP2 KO mice was accomplished with lower amounts of proinflammatory cytokines in the lungs. This led to an abolished recruitment of neutrophils into the lungs, the spread of bacteria and the subsequent aggravated course of the disease and early mortality of the PGLYRP2-KO mice. These data suggest a substantial role of PGLYRP2 in the early defense against S. pneumoniae infection, and PGLYRP2 might also affect other infections in the lungs.